BREAKING THE BARS: BODY AND IDENTITY IN ANITA NAIR’S LADIES COUPE - M. K., Anjaly Nair (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Body has become a subject of serious discussion in the contemporary society where there are stern debates on body shaming, body autonomy, self- objectification, body positivity, fatphobia etc. One’s body is closely related to the formation of one’s identity. Normally, in literature, female body is always portrayed as ‘objects’, aiming to please and satisfy the male gaze. Anita Nair in her Ladies Coupe describes how the same body which is intended to satisfy the male gaze can be used to satisfy oneself thereby forming an identity, which is free from the identity constructed by the patriarchal society. Nair describes the life of six fellow travellers in a ladies coupe who disclose various personal incidents in their life. The women in the coupe are from various sections of the society, are in different phases of life, but are victims of patriarchy in one way or another. Nair narrates how these women, who were once victims of male domination, uses their body in order to revenge against the male members under whom they suffered.